Siostra miłosierdzia contra niebezpieczna morderczyni. Motyw pielęgniarki w thrillerach medycznych = A sister of mercy versus a dangerous murderer. Nurse theme in medical thrillers - Trześniewska-Nowak, Agnieszka (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The nurse's role in literature seems to be marginalised. Nurses constitute a margin, especially in medical thrillers, in which men dominate the hospital world. The books' characters, such as Robin Cook's, call the nurses "the lower-level staff". The transfer of optics from men-doctors to women nurses raises an important issue of social roles and stereotypes that has been grounded in literature for years.
Keywords: thriller medyczny; medycyna; pielęgniarki; morderstwo; medical thriller; medicine; nurse; murder